Mimpi Yakub Di Betel Kejadian 28:10-22 Dan Simbol Simbuang Batu Dalam Ritual Rambu Solo’ Di Toraja Sebagai Upaya Anamnesis Dan Mimesis - Angely Daniel (Jurnal Teologi Pambelum, 2024)
Jacob's Dream at Bethel in Genesis 28:10-22 is the story of Jacob's journey from Beersheba to Haran. During the journey from Beersheba to Haran Jacob had a dream, God appeared in the dream stating promises and blessings upon him. After he had the dream he woke up from his sleep to erect a stone monument and declared the place to be a symbol of the house of God. Based on the story of Jacob who erected the stone, in Toraja tradition there is also a rite of simbuang batu or menhir. In the implementation of the Rambu Solo' ritual or death ceremony, a rite of erecting a simbuang batu or menhir is carried out in the rante, namely the yard where the Rambu Solo' ritual is carried out. This study aims to determine Jacob's dream at Bethel Genesis 28:10-22 and the symbol of simbuang batu in the Rambu Solo' ceremony ritual as an effort of anamnesis and mimesis. The author intends to use a qualitative research method. Qualitative research is used as an effort by researchers to explore information and analyze the meaning and value of an object being studied. Data collection techniques are carried out through literature studies and interviews. The author has conducted interviews with several sources who understand the simbuang batu ritual in the Rambu Solo' ceremony ritual in Toraja. The results of the study indicate that Jacob's Dream in Bethel is a symbol of God's presence expressed by Jacob through the symbol of the establishment of a stone monument as the house of God which expresses His presence and love. In line with that, the Toraja people understand simbuang batu as a symbol of love and affection in family relationships. As an effort of anamnesis and mimesis, the author is interested in writing about this topic.